IT Influence on the Functioning of the Tourist Market - Żegleń, Patrycja; Nizioł, Anna (Studia Oeconomica Posnaniensia, 2017)
The tourist sector is among those economy branches in which one demands fast and fluent information transfer - its generating, colleting, processing, and providing. The increasing demand and qualitative expectations of today's clientstourists create the necessity of introducing IT in the range of distribution channels, promotional tools, tourist products as well as cooperation with other organizations. The aim of the paper is to present modern technologies used in tourism branches, especially in airlines, travel agencies, and the hotel industry. Additionally, the aim is to show the influence of IT tools on the tourist market. The research methodology was based on the desk research method, including verifying widely used sources such as professional literature, web research, statistical data etc. Research data have a qualitative, quantitative, primary and secondary character. The authors used various research techniques such as: CATI (Computer Assisted Telephone Interview) and CAPI (Computer Aided Personal Interview) and also a survey questionnaire. The primary research results concern the meaning of IT tools for the tourist market. The secondary research results concern the use of communication and information technologies with examples of TripAdvisor.com or eSKY.pl. The research results focus on the role IT plays on today's tourist services market.